Assessing EFL Undergraduate Students’ Needs for the Development of Writing Learning Materials - Gultom, Uli Agustina (STAIN Majene, 2025)
Learning materials are important components of the language teaching and learning process, including the writing course. To develop writing learning materials, particularly for higher education, it is crucial to identify the students’ writing needs. As the initial step in developing learning materials to support teaching writing, this study aims to investigate undergraduate students' current abilities and needs, as well as the appropriate ICT tools. The study for needs assessments was responded by 184 English department students from various Indonesian universities and six of them were interviewed. The findings indicated that students of various capacities have the desire to acquire knowledge and improve their writing skills. The results highlight the undergraduate students' learning experiences and insufficient writing abilities, with problematic areas in grammar and the organization of ideas, as well as challenges in writing independently during the learning process. In addition, teachers should either have or improve their pedagogical expertise and be adaptive to the evolution of information and technology to fulfill the needs indicated by students. Further study is needed to take the next step toward developing and providing learning materials with a range of activities, assignments, assessments, and applications to excite students' interest and engagement in the writing course.